2022
DOI: 10.31235/osf.io/fsv7n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public Residential Charging of Electric Vehicles: an exploration of UK user preferences

Abstract: In this study, we investigate the preferences for private electric vehicle (EV) charging among households without a private residential charging option. We seek to understand which attributes of a residential neighbourhood charging service would offer an attractive substitute to charging an EV on private property overnight, as is most common among existing EV owners. Our stated choice experiment is designed to reflect preferences for parking as well as charging behaviour in order to ground the choices in trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Three Parking Enforcement Officers were asked in one study to identify the best streets for on-street recharging for people without driveways [83]. Of 2001 participants in a study in the UK who did not have a driveway or garage, 44% preferred on-street charging, and 56% wanted hub charging options, such as a car park [84]. The respondents also wanted a safe and attractive route to walk from their parked car to home.…”
Section: Results Confirm or Contrast With Literaturementioning
confidence: 99%
“…Three Parking Enforcement Officers were asked in one study to identify the best streets for on-street recharging for people without driveways [83]. Of 2001 participants in a study in the UK who did not have a driveway or garage, 44% preferred on-street charging, and 56% wanted hub charging options, such as a car park [84]. The respondents also wanted a safe and attractive route to walk from their parked car to home.…”
Section: Results Confirm or Contrast With Literaturementioning
confidence: 99%
“…At present, most studies investigating charging habits include only few social and demographic groups, excluding many potential users who may have different charging needs and attitudes. Further exploration is needed on the issue of different charging preferences based on gender [71,144]. Despite charging infrastructure manufacturers' efforts to make their systems compliant with the needs of disabled individuals, there has been no research (that the current authors are aware of) conducted on the charging needs and preferences of impaired people.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot experiment on dedicated neighborhood charging [70] showed that potential EV users consider parking-combined and bookable charging options within the city to be of paramount importance, especially as parking is a problem common to both EV users and non-EV users. A survey of stated preferences without a private residential charging option found that the most important aspects of public charging are closely related to personal safety and proximity to one's home, especially if the service is used overnight [71].…”
Section: Socio-demographic and Psychological Aspectsmentioning
confidence: 99%
See 2 more Smart Citations